The effect of immigration on human capital expenditure in Europe: an international analysis - Günel, Tuğay; Gedlik, Akdoğan (Publishing House of Wroclaw University of Economics and Business, 2022)
Immigration into Europe has been increasing rapidly in recent years, and consequently the European Union is intensifying efforts to create an effective and safe migration policy. In this context, European institutions play a crucial role in setting strategic instruments for migration policy, and the adaptation and integration process of immigrants is one of these instruments. For this purpose, EU countries are implementing various human capital outlays, e.g. on public education and healthcare. This study aimed to empirically analyse the impact of immigration on this expenditure. Panel data analysis was carried out with the data between 1995 and 2017 for 16 European countries. The results support the argument that immigration may have reduced the expenditure that immigrants benefit more from, such as education and social expenditure, while it does not reduce the expenditure that immigrants benefit less from such as healthcare.
Argumenta Oeconomica, 2022, Nr 1 (48), s. 67-80
Keywords: immigration; human capital expenditre; panel data analysis